Finite elements in fluids (John Wiley & Sons, 1974)
Vols. for 1975 contain selected papers from the International Symposium on Finite Element Methods in Flow Problems; vols. for 1976- contain selected papers from the International Conference on Finite Elements in Flow Problems.